(untitled) (Jurnal Bahasa, 2003)
This article attempts to elaborate upon information structure as an aspect in discourse focussing on Malay Folktales. The observation of information arrangement and intonation as a marker of information type, as suggested by Halliday ( 1985), was attempted on two separate folktales.